AN ARGUMENTATIVE ANALYSIS OF SIR KEN ROBINSON IN TED TALK - Sri Sri; Saifuddin Ahmad Husin; Sovia Rahmaniah (LET: Linguistics, Literature and English Teaching Journal, 2019)
This research used argumentative discourse which is aimed to find out components of argument and structures of argument that is used by Sir Ken Robinson in TED Talk. Toulmin’s model and Cohen’s theory were used to recognize the components and structures of arguments. The data used for analysis were videos and the transcripts. There are two videos which are being analyzed; “Bring on the Learning Revolution” and “Do School Kill Creativiy?”. It presented five data analysis procedures: compiling (choosing data), disassembling (compling data into smaller potion and coding), reassembling (indicating to categories), interpreting( analyzing the data and explaining the data), and concluding (drawing conclusion) The result revealed that from both videos “Bring on the Learning Revolution” and “Do School Kill Creativiy?”, there were several components components that are used; claim, data, and warrant were 100% used in all arguments, qualifier was 55, 56%, rebuttal was 27,80%, and backing was 88,90%. For the structure of arguments that is used by Sir Ken Robinson in both his videos the percentage coherent structure of pre-order was 66,7%, for post-order was 22,2%, and for hybrid was 11,1%. Then, for linguistic clue showed that re- direction clue had 16,7% then connectives had 83,3%. and evidence relationship had 100%.